2020
DOI: 10.1177/0004563219899421
|View full text |Cite
|
Sign up to set email alerts
|

In-house age-specific reference ranges for free light chains measured on the SPAPlus® analyser

Abstract: Background The measurement of monoclonal free light chains is being increasingly utilized since the introduction of serum-based assays. It is important for laboratories to determine their own reference ranges in order to reflect the local population. The aim of this study was to determine if age-adjusted reference ranges for serum free light chains would have implications for demand management of further laboratory investigations including immunofixation. Methods After certain exclusions, 4293 samples from ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…In line with earlier studies ( 45 , 47 , 48 ), we demonstrated that serum κFLC levels increased with age. While serum κFLC concentrations have shown to be stable in samples stored at −20°C for at least a year ( 49 , 50 ), the stability of CSF κFLC remains unexplored.…”
Section: Discussionsupporting
confidence: 93%
“…In line with earlier studies ( 45 , 47 , 48 ), we demonstrated that serum κFLC levels increased with age. While serum κFLC concentrations have shown to be stable in samples stored at −20°C for at least a year ( 49 , 50 ), the stability of CSF κFLC remains unexplored.…”
Section: Discussionsupporting
confidence: 93%